Answer :

It is given in the question that,

=

=

=

=

=

= [- 1 – i]^{3}

= (- 1)^{3} [1 + i]^{3}

= - [1^{3} + i^{3} + 3 × 1 × i (1 + i)]

= - [1 + i^{3} + 3i + 3i^{2}]

= - [1 – i + 3i – 3]

= - [- 2 + 2i]

**= 2 – 2i**

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

If z and w are twMathematics - Exemplar

State True of FalMathematics - Exemplar

State True of FalMathematics - Exemplar

State True of FalMathematics - Exemplar

Solve for x: (1 –RS Aggarwal - Mathematics

Find the real valRD Sharma - Mathematics

If n <span lang="RD Sharma - Mathematics

Write the least pRD Sharma - Mathematics

If <span lang="ENRD Sharma - Mathematics

If n is any positRD Sharma - Mathematics